2023
DOI: 10.3390/su15076003
|View full text |Cite
|
Sign up to set email alerts
|

Industry and Regional Peer Effects in Corporate Digital Transformation: The Moderating Effects of TMT Characteristics

Abstract: Currently, the research on corporate digital transformation is mainly explored from the perspective of independent decision-making, but pays less attention to the interactive impact among peer firms. Taking the listed equipment manufacturing enterprises in China as its research sample, this paper uses theoretical analysis and empirical tests to test the impact of peer effect in corporate digital transformation and the moderating effect of top management team (TMT) characteristics. The results show that there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…On the one hand, the historical informatization level has nurtured and influenced the modern Internet, but the city's historical informatization level does not directly affect the CSR performance of local corporates. In addition, previous literature has shown that digital transformation has a cohort effect (Zhang & Du, 2023), peer corporates have the general characteristics of the industry and may have similar needs in the application of digital technology, but the digital transformation of other corporates generally cannot directly affect the corporate social responsibility performance. Based on the above analysis, the instrumental variables selected in this paper meet the requirements of relevance and exclusivity.…”
Section: Empirical Analysismentioning
confidence: 99%
“…On the one hand, the historical informatization level has nurtured and influenced the modern Internet, but the city's historical informatization level does not directly affect the CSR performance of local corporates. In addition, previous literature has shown that digital transformation has a cohort effect (Zhang & Du, 2023), peer corporates have the general characteristics of the industry and may have similar needs in the application of digital technology, but the digital transformation of other corporates generally cannot directly affect the corporate social responsibility performance. Based on the above analysis, the instrumental variables selected in this paper meet the requirements of relevance and exclusivity.…”
Section: Empirical Analysismentioning
confidence: 99%
“…These characteristics are indicative of the thinking and value systems of the TMT members, which then affect the actions and choices of the corporation. The decision-making process and the implementation of corporate DGT initiatives are both highly dependent on the role of the TMTs [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TMT characteristics are strongly linked to managers' incentives such as avoiding risk, copying others, and competing. These characteristics have a significant influence on information sharing and resource obtaining that are essential for effective corporate DGT efforts [41,[44][45][46][47][48][49][50]. The characteristics of the TMT members, which are both compatible and cohesive, are often seen as a dynamic interaction that drives the innovation process.…”
Section: Introductionmentioning
confidence: 99%
“…Third, in practice, the decision-making of serial M&A has great uncertainty, and the research of this paper has important guiding significance for understanding the serial M&A decision-making relationship among geographical peer firms in China. Under the uncertain economic policy environment and incomplete and asymmetric investment information, the geographical peer effect is common [ 44 ]. In the Chinese capital market, many examples of social interaction among geographical peer firms, groups, and individuals observe, imitate, and learn from each other, resulting in consistent behavioral decisions among peers.…”
Section: Introductionmentioning
confidence: 99%